A Radiographic Analysis of Lumbar Fusion Status and Instrumentation Failure After Complex Adult Spinal Deformity Surgery With Spinopelvic Fixation: Two-Year Follow-up From the Scoli-Risk-1 Prospective Database. Issue 10 (December 2020) - Shimizu, Takayoshi; Lenke, Lawrence G.; Cerpa, Meghan; Beauchamp, Eduardo C.; Carreon, Leah Y.; Shaffrey, Christopher I.; Cheung, Kenneth M.C.; Fehlings, Michael G.
Abstract : Study Design: A retrospective review of prospectively collected data. Objective: The objective of this study was to investigate the fusion status of the lumbar spine and lumbosacral junction at 2 years postoperatively after complex adult spinal deformity (ASD) surgery. Summary of Background Data: Achieving fusion is crucial for maintaining optimal alignment in ASD surgery. However, prospective data assessing fusion status using large patient populations are lacking in this patient population. Materials and Methods: Postoperative radiographs of 162 patients from the Scoli-Risk-1 database, who underwent complex ASD surgery with fusion to the sacrum, were evaluated by 3 independent spine surgeons at 6-week, 6-month, and 2-year follow-up. The fusion rate of the lumbar spine segments at a 2-year follow-up was determined by using previously published radiographic grading criteria. We also assessed the prevalence of instrumentation failures. Results: The interrater reliabilities for grading the fusion status were overall fair at each level evaluated (Fleiss κ, 0.337–0.439). Overall, 70.3% (114/162) demonstrated the solid fusion of the entire lumbar spine at a 2-year follow-up. The fusion rates of each segment were L1/L2: 87.0%, L2/L3: 82.0%, L3/L4: 83.9%, L4/L5: 89.5%, and L5/S1: 89.5%. Pedicle screw loosening was the most frequent implant failure throughout the observation period (9.2%, 11.6%, and 11.0% at 6-wk, 6-mo, and 2-y follow-up, respectively). No rod breakage was observed at 6 weeks, increasing to 9.8% at 2-year follow-up. The prevalence of postoperative proximal junctional kyphosis was 5.5% at 6 weeks, showing no difference at 2 years postoperative. Conclusions: In this series of complex ASD surgeries often requiring 3-column osteotomies, 70.3% showed solid fusion of the entire lumbar spine, including the lumbosacral junction. The lumbosacral segments showed a relatively high fusion rate at a 2-year follow-up likely due to the frequent use of anterior column support and graft. The prevalence of rod breakage increased as follow-up proceeded to 9.8%, which was most commonly observed at the lumbosacral junction. Level of Evidence: Level IV.